Distinct regulatory roles of transforming growth factor-beta and interleukin-4 in the development and maintenance of natural and induced CD4+ CD25+ Foxp3+ regulatory T cells - Prochazkova, Jana; Fric, Jan; Pokorna, Katerina; Neuwirth, Ales; Krulova, Magdalena; Zajicova, Alena; Holan, Vladimir (Immunology, 2009)
The development and function of CD4(+) CD25(+) Foxp3(+) regulatory T cells (Tregs) are strictly regulated by cytokines. Here we show that transforming growth factor-beta (TGF-beta) and interleukin-4 (IL-4) play a crucial and antagonistic role in the development of Tregs. Additionally, these cytokines also have distinct effects on the maintenance of natural (nTregs) and antigen-induced (iTregs) Tregs. Using double-staining and tracking of proliferation of purified and carboxyflourescein succinimidyl ester (CFSE)-labelled mouse T-cell subpopulations we demonstrated that CD4(+) CD25(+) Foxp3(+) iTregs develop upon alloantigenic stimulation in the presence of TGF-beta exclusively from CD4(+) CD25(-) Foxp3(-) precursors. Both the induction of Foxp3 expression and Treg proliferation were prevented when the cells were stimulated in the presence of IL-4. By contrast, nTregs did not proliferate in the presence of the antigen and TGF-beta, and partially lost their Foxp3 expression. IL-4 not only prevented the development of iTregs, but also down-regulated the level of Foxp3 mRNA and decreased the number of Foxp3(+) cells in a population of iTregs. Further analyses proved that IL-4 decreased the expression of Foxp3 only in a population of iTregs, whereas it substantially supported the survival of nTregs. Functional experiments showed that Tregs induced in the presence of alloantigen and TGF-beta inhibited, on a per-cell basis, cell proliferation comparably to nTregs, and their suppressive capacity was not modulated by IL-4. These data suggest that TGF-beta and IL-4 differentially regulate the development of Tregs and distinctly sustain Foxp3 expression and the number of nTregs and iTregs, but have no influence on the suppressive activity of Tregs on a per-cell basis.
Keywords: RNA, Messenger; T-Lymphocyte Subsets; Male; forkhead transkripční faktory; Transforming Growth Factor beta; regulační T-lymfocyty; buněčná diferenciace; myši inbrední BALB C; Forkhead Transcription Factors; mužské pohlaví; T-lymfocyty - podskupiny; interleukin-4; Mice, Inbred BALB C; Interleukin-4; transformující růstový faktor beta; T-Lymphocytes, Regulatory; CD4-Positive T-Lymphocytes; Animals; ženské pohlaví; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; Mice; Female; messenger RNA; CD4-pozitivní T-lymfocyty; Cell Differentiation